Relationship between learning ecology and self-regulated learning in a General Chemistry course - Carazo Mesén, Jenncy (2025)
Learning ecologies that integrate various technological and pedagogical resources encourages self-regulated learning and promotes students’ ability to take control of their own learning process. This results in the ability to set goals, plan, monitor, and assess their progress. This article presents part of the results obtained from the implementation of a learning ecology in a General Chemistry university course at the Interuniversity Campus of Alajuela - University of Costa Rica, during the first semester of 2023. The objective is to analyze the type of correlation existing between learning ecology and self-regulated learning, establishing the relationship of technological resources that make up the learning ecology within the phases of self-regulated learning. The research follows a mixed-method approach with a concurrent embedded design of a dominant model. A total of 70 students were enrolled in the learning ecology, with the entire population participating in the quantitative phase, while a nested sample took part in the qualitative phase. The results show a positive correlation between learning ecology and self-regulated learning, as students with higher levels of self-regulated learning exhibit preferences and more effective use of technological resources according to the phase of self-regulated learning. It is concluded that the implementation of various technological resources within a learning ecology provides students with flexibility and autonomy to manage their learning. Promoting the use of learning ecologies as an alternative support in university courses not only enriches the learning process but also develops critical skills for academic and professional success.